P272 Predictors of health-related quality of life in patients with newly diagnosed moderate to severe ulcerative colitis: Results from the MOSAIC cohort in Korea. (16th January 2018) - Park, Y M; Lee, C K; Hong, S N; Im, J P; Ye, B D; Cha, J M; Cha, J M; Jung, S -A; Lee, K -M; Park, D I; Jeen, Y T; Park, Y S; et al.
Abstract: Background: There are limited data regarding disease burden and patient-reported outcomes (PROs) of inflammatory bowel disease in non-Western countries. The MOSAIK cohort is a Korean nationwide, multi-centre, hospital-based inception cohort to reveal disease behaviour and long-term outcome in patients with newly diagnosed moderate to severe ulcerative colitis (UC) (ClinicalTrials.gov id: NCT02229344). We aimed to identify predictors of health-related quality of life (HRQoL) and to document burden of psychosocial distress shortly after disease onset in patients affiliated with the MOSAIK cohort. Methods: Between August 2014 and March 2017, 355 consecutive patients were enrolled to the MOSAIK cohort. All patients were requested to complete four self-questionnaires within the first 4 weeks of diagnosis, including (1) 12-item short-form health survey (SF-12) and Inflammatory Bowel Disease Questionnaire (IBDQ) for HRQoL, (2) work productivity and activity impairment (WPAI) questionnaire for work disability, and (3) Hospital Anxiety and Depression scale (HADS) for emotional health. Linear regression analysis was used to evaluate predictive factors of HRQoL. Another logistic regression model was used to evaluate predictors of poor disease-specific QoL defined as total IBDQ score <170. Results: In total, 59.2% (210/355) were male and the mean age was 37.6 years. Disease severity and extent were found to be major determinants of HRQoL in the linear regression. Severe disease was associated with poor social function and low total IBDQ score as well as low mental health score of the SF-12 (all p < 0.05). Extensive disease was associated with low levels of all domains of the IBDQ (excluding bowel system) and low mental/physical health scores of the SF-12 (all p < 0.05). When using predefined criteria (total IBDQ score <170), 78.1% (274/351) of patients was reported as having poor disease-specific QoL. Substantial numbers of patients have significant mood disorders as 16.7% for anxiety and 20.6% for depression (≥11 by HADS). About half of patients have severe work disability as work impairment for 46.2% and social activity impairment for 53.5% (≥50% by WPAI). Higher disease activity was a significant predictor of poor disease-specific QoL: odds ratio 1.50, 95% confidence interval 1.228–1.841 in the logistic regression. Conclusions: Patients with newly diagnosed moderate-to-severe UC have a significant burden of poor QoL, psychological comorbidity and work disability within the first 4 weeks of their diagnosis. Disease severity and extent are useful predictors of HRQoL in these patients. Our results suggest that it is required to integrate HRQoL and other PRO measures into the routine initial assessment.